Channel Length Modeling and Experimental Demonstration of Adaptive Threshold Under-Sampled CamCom for Low-SNR Transmitters - Muhammad Asim Atta; Babar Hussain; Amine Bermak (IEEE Photonics Journal)
Under-sampled camera communication (CamCom) systems realized using fast shutter speeds limit the communication channel length and impose restrictions on the minimum signal-to-noise ratio (SNR) requirement of LED based transmitters. In this paper, we present an empirical model to estimate the effective channel length of a CamCom system. Based upon the model, a transceiver methodology is proposed and demonstrated to support low-SNR transmitters, thereby increasing the effective communication distance of an under-sampled CamCom link. Moreover, an adaptive threshold decoding technique is presented to make the system robust against the variable frame rate phenomenon. The proposed methodology can be utilized to increase the communication distance of under-sampled CamCom links for infrastructure-to-vehicle communication employing low-SNR transmitters.